Monitoring Knee Biomechanics in Patients Undergoing Anterior Cruciate Ligament Reconstruction: How Joint Loading Affects Cartilage Quality. (2019) - Marchiori, G.; Cassiolas, G.; Berni, M.; Lopomo, N.F.; Valente, G.; Signorelli, C.; Bontempi, M.; Zaffagnini, S.
Abstract: Rupture of anterior cruciate ligament (ACL) is a common injury, generally treated by reconstruction surgery. Despite good clinical outcomes, achieving a long-term success for this procedure is still a challenge: young patients could face in fact early degenerative processes, including knee osteoarthritis (OA). The altered biomechanics of the reconstructed joint could affect knee anatomical structures varying – for instance – the loads on the intra-articular cartilage, definitely inducing its degeneration. To better understand the factors that can compromise the long-term success of this procedure, this study investigated the ACL transtibial reconstruction effects on overall knee biomechanics and on articular cartilage, by integrating dynamic radiostereophotogrammetry, inferior limb multi-body modelling and MRI T2 mapping, in order to correlate knee joint loads to its physiopathological status